Trans cohort metabolic reprogramming towards glutaminolysis in long-term successfully treated HIV-infection - Flora Mikaeloff; Sara Svensson Akusjärvi; George Mondinde Ikomey; Shuba Krishnan; Maike Sperk; Soham Gupta; Gustavo Daniel Vega Magdaleno; Alejandra Escós; Emilia Lyonga; Marie Claire Okomo; Claude Tayou Tagne; Hemalatha Babu; et al. (Communications Biology, 2022)
Mikaeloff et al. use untargeted and targeted LC-MS/MS-based plasma metabolic profiling to discover dysregulated metabolism including that of glutaminolysis in individuals living with HIV. Furthermore, decreased levels of neurosteroids were detected suggesting a potential connection between HIV and neurological impairment.